Effects of one's sex and sex hormones on sympathetic responses to chemoreflex activation. Issue 3 (14th December 2015) - Usselman, Charlotte W.; Steinback, Craig D.; Shoemaker, J. Kevin
Abstract : New Findings: What is the topic of this review? This review summarizes sex‐dependent differences in the sympathetic responses to chemoreflex activation, with a focus on the role of circulating sex hormones on the sympathetic outcomes. What advances does it highlight? The importance of circulating sex hormones for the regulation of sympathetic nerve activity in humans has only recently begun to be elucidated, and few studies have examined this effect during chemoreflex regulation. We review recent studies indicating that changes in circulating sex hormones are associated with alterations to chemoreflex‐driven increases in sympathetic activity and highlight those areas which require further study. Sex‐dependent differences in baseline sympathetic nerve activity are established, but little information exists on the influence of sex on sympathetic activation during chemoreflex stimulation. In this article, we review the evidence for the effect of sex on chemoreflex‐driven increases in sympathetic nerve activity. We also review recent studies which indicate that changes in circulating sex hormones, as initiated by the menstrual cycle and hormonal contraceptive use, elicit notable changes in the muscle sympathetic activation during chemoreflex stimulation. Abstract :